TATA KELOLA KEUANGAN NEGARA DALAM INVESTASI CRYPTOCURRENCY OLEH DANANTARA:TINJAUAN MAQHASID SYARIAH - Nawaz Syarif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
As technology adoption accelerates and global cryptocurrency popularity rises, countries are beginning to view cryptocurrencies as strategic alternative investments. In Indonesia, Danantara has emerged as a Superholding institution and Sovereign Wealth Fund managing state-owned assets on a large scale. Investments in crypto assets like Bitcoin offer high-profit potential but also carry significant risks that could lead to state losses. This study highlights the urgency of synergy among institutions such as the Ministry of Finance, Bank Indonesia, the Audit Board (BPK), and the Financial Services Authority (OJK) in building a transparent oversight and accountability system. Additionally, the author emphasizes the need for clear regulations regarding Danantara's accountability in the event of investment losses, especially considering the high volatility of crypto asset values and the absence of explicit rules protecting state financial interests. This study aims to provide a solid legal and governance foundation to minimize fiscal risks and ensure the professional and responsible management of public investments. This aligns with the principles of Maqhasid Syariah, which includes the meaning of protecting wealth in the context of national wealth